Museum Ragam Hias Melayu Riau Di Pekanbaru Dengan Penekanan Pelestarian Dan Pengembangan Ragam Hias Melayu Riau - Malicha Dini Anjani; Ratna Amanati; Muhammad Rijal (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2014)
Malay Ornament Museum Of Riau is the specialized museum that contains a collection of Malay decorative and ornament. Ornament that is stored in the museum is an architectural ornament or Riau public used in buildings (arts of Malay). Storage categories of decoration is divided into two, namely in the form of carvings and ancient manuscripts. In the design of this Ornament Museum, the main concern is the circulation in the exhibition space. Circulation must be created to make visitors enjoy all the collection without feeling bored and exhausted. In addition to circulation, to reinforse the theme of the museum, the building uses the concept of transformation of traditional Malay architecture in order to wither atmosphere can be felt throughout the building.Keyword: museum, ornament, Riau Traditional Malay.